1999
DOI: 10.1007/s004360050616
|View full text |Cite
|
Sign up to set email alerts
|

A novel cDNA clone encoding a specific excretory/secretory antigen of larval Trichinella pseudospiralis

Abstract: A cDNA library for Trichinella pseudospiralis was constructed to study the expression of speci®c antigens. Four positive clones were identi®ed using antibodies against the excretory/secretory (ES) products of the nematode as probe. Sequence analysis showed that they contained identical cDNA inserts of 606 bp, including a 5¢ non-translated region of 96 bp, a core translated segment of 408 bp and a poly(A) + 3¢ terminus. It encoded a novel 136-amino-acid polypeptide. Southern blot analysis indicated that the cDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…pseudospiralis-specific 15-kDa protein Chung and Ko (1999) reported that the protein with a molecular weight of 15 kDa is present in E-S products of T. pseudospiralis. This protein exists only in the stichocytes of T. pseudospiralis and not in T. spiralis.…”
Section: Tsj5 Proteinmentioning
confidence: 99%
“…pseudospiralis-specific 15-kDa protein Chung and Ko (1999) reported that the protein with a molecular weight of 15 kDa is present in E-S products of T. pseudospiralis. This protein exists only in the stichocytes of T. pseudospiralis and not in T. spiralis.…”
Section: Tsj5 Proteinmentioning
confidence: 99%
“…Moreover, the ES antigens or recombinant ES antigens of several parasites are reported to be useful in serodiagnosis (Chung and Ko 1999;D¢Souza and Hafeez 1999;Mehta et al 1999;Sadjjadi et al 2000;Yamasaki et al 2000;Carnevale et al 2001). The ES antigens of adult C. sinensis were investigated for use in serodiagnosis and it was reported that a 12.5-kDa and a 7-kDa antigen might serve as markers of active clonorchiasis (Kim 1994(Kim , 1998.…”
Section: Introductionmentioning
confidence: 98%
“…The excretory-secretory products (ESP) are known to involve in parasite-host interaction (Nagano et al 2009), and clinical significance in the diagnosis and pathogenesis (Chung and Ko 1999;Santra et al 2000;Yamasaki et al 2000). ESP play key roles in C. sinensis adults migrating to the intrahepatic bile ducts and subsequent cholangiocarcinoma (Kim et al 2009b;Pak et al 2009).…”
mentioning
confidence: 98%